Pengaruh Perkembangan Infrastruktur Dasar Pariwisata Terhadap Minat Kunjungan Wisatawan Candi Gedong Songo Kecamatan Bandungan - Fiki Putri Kartika; Hadi Wahyono (Teknik PWK (Perencanaan Wilayah Kota), 2019)
The development of infrastructure quality can produce tourism object development, which can attract more tourists). This study aims to analyze the effect of the development of basic tourism infrastructures on the tourists visiting the Gedong Songo Temple with linear regression analysis tools. The variables used are the number of tourists as (dependent variable) and roads, clean water, electricity, telecommunications and waste infrastructures as (independent variables). The results show there is an influences between the development of infrastructure in the interest of tourist visits, where the infrastructure indicators that influenced the interest of tourist visits are the number of electricity customers and the length of the road in good condition with the resulting model. Y = 2,509 X1 + 38,349X3 + €i it means that an increase in the length of the road network in good condition 1 Km that is good can affect the growth of tourist interest by 2,509 residents. there is an increase in the number of electricity customers by 1 person it can affect the growth of tourist interest by 38,349 people. These results can explain that effect of the development of basic tourism infrastructures on tourist visits by 92.9%, while the rest is influenced by other factors not explained or voiced in this study.